Incorporating the Rome statute in the Malaysian national legal system: issues and challenges - Hamid, Abdul Ghafur@Khin Maung Sein (2019)
The instrument of accession to the Rome Statute was deposited with the Secretary-General of the United Nations on 4 March 2019. The Statute will enter into force for Malaysia on 1 June 2019. However, the Rome Statute will not become law in Malaysia unless and until it has been transformed into the Malaysian national legal system by legislation made by Parliament. The main objective of the paper is to appraise the way how the Rome Statute can be incorporated in the Malaysia legal system. The paper concludes that Malaysia should follow the majority of state parties to merge the two purposes of criminalizing the four international crimes in the Malaysian domestic law and to cooperate with the ICC. The paper also suggest to empower the High Court to have jurisdiction over these crimes.